Konsep Komunikasi dalam Kisah Ashabul Kahfi : (Analisis Interpretasi QS. Al-Kahfi Ayat 10 - 21) - Ita Silviani; Amir Mahmud; Miftara Ainul Mufid; M. Mukhid Mashuri (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The Qur'an provides guidance through stories, including the story of Ashabul Kahfi in Surah Al-Kahfi Verses 10, 11, 14, 15, 16, 19, 20, 21 which describes communication between the young men in difficult situations. This study aims to examine the concept of communication in the story, including the form, value, and scope of communication carried out by the young Ashabul Kahfi. The method used is the Tahlili Method, by analyzing the meaning of the verses, asbabun nuzul, munasabah between verses, as well as the mufradat and beauty of the Arabic language in the verses. The results of this study indicate that the story of Ashabul Kahfi contains types of communication in the form of verbal when discussing between young men, and non-verbal when running away from King Diqyanus. The form of communication in this story includes transcendental communication in the form of prayer to Allah. In addition to the types of communication in the story of Ashabul Kahfi, the author also found the principle of their honesty when communicating with King Diqyanus when asking about their faith, so that it can give birth to a concept of communication that prioritizes honesty, courage and solidarity.